2013
DOI: 10.1016/j.adolescence.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal development, physical self‐perception, and motivation toward physical activity in girls

Abstract: We examined the differences in physical self‐perception and motivation toward physical activity in early‐ and mid‐adolescent girls. Body Mass Index (BMI) and pubertal status, assessed by means of the Tanner scale, were collected in 11‐year‐old (n = 74) and 13‐year‐old girls (n = 60). The assessment included six scales from the Physical Self‐Description Questionnaire, the Physical Activity Enjoyment Scale, and the Situational Intrinsic Motivation Scale. Age differences emerged, with older girls showing a poorer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 49 publications
2
49
2
5
Order By: Relevance
“…In particular, the development of muscle strength in children is related to factors such as age, body size and sexual maturation [12,15]. In terms of psychological profile, puberty shows changes in motivation, cognitive and socio-emotional characteristics [16,17]. In addition, various studies [18,19] have shown that boys and girls responded differently to puberty and that post-pubertal boys have a better psychosocial adjustment than pre-pubertal boys.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the development of muscle strength in children is related to factors such as age, body size and sexual maturation [12,15]. In terms of psychological profile, puberty shows changes in motivation, cognitive and socio-emotional characteristics [16,17]. In addition, various studies [18,19] have shown that boys and girls responded differently to puberty and that post-pubertal boys have a better psychosocial adjustment than pre-pubertal boys.…”
Section: Introductionmentioning
confidence: 99%
“…Labbrozzi et al (2013) em estudo com adolescentes italianas, identificou que a medida que crescem, apresentam uma diminuição da motivação pela atividade física e menor auto percepção física, da competência esportiva e do conceito físico global. Carraro et al (2010) também investigando adolescentes italianos, verificou que o aumento do IMC parece influenciar não só as percepções, mas também, de forma negativa, sobre o indivíduo na percepção da coordenação.…”
Section: Discussionunclassified
“…Dimensão psicológica Dos três estudos selecionados (Carraro et al, 2010;Labbrozzi, Robazza, Bertollo, Bucci, & Bortoli, 2013;Vera et al, 2012), os dois primeiros utilizaram o PSDQ (Physical SelfPerception Questionnaire) para avaliar a autoconceito físico e a bateria de testes EUROFIT para mensurar a aptidão física. Carraro et al (2010), ao comparar os resultados dessa bateria com os obtidos no PSDQ, observou, que o IMC parecia não influenciar só as percepções, mas também e de forma negativa a percepção da coordenação do indivíduo.…”
Section: Legendaunclassified
See 1 more Smart Citation
“…Furthermore, this may compound with age. Labrozzi et al (2013) found that, compared with younger girls, 13-year-olds had a poorer physical perception, lower intrinsic motivation, and enjoyment of physical activity. It is not known whether the coupling of being female and having low motor competence creates a further disadvantage for girls' self-perceptions in early adolescence.…”
Section: Introductionmentioning
confidence: 99%